The ethnographic present revisited - Pina-Cabral, Joao (2021)
The old methodological injunction to focus on the ethnographic present has been taken negatively to mean a refusal of history. In this paper, I propose that the notion of ethnographic present be used conjecturally to reflect the situated nature of all ethnographic research.